Depictions Of Arab World In The Arab-American Poet Naomi Shihab Nye’s Select Poetry - Tribhuwan Kumar; Abdelrauof Alharahsheh (Ijaz Arabi Journal of Arabic Learning, 2026)
The study aims to determine how Arab-American authors Naomi Shihab Nye and Diana Abu-Jaber depict Arabs in their selected poems including "Half and Half", "Fuel”, "Kindness", "19 Varieties of Gazelle", “The Sweet Arab, the Generous Arab”, "For Mohammed Zeid of Gaza, 15 Years Old" and  “An Ode to The Sweet Arab, the Generous Arab”.  Naomi Shihab Nye is an Arab-American poet residing in Texas, where she interacts with many diasporas. She has sustained a friendship with Palestine for fourteen years.  Her empathy for her father, Aziz, acts as the impetus for her writing. Moreover, her mother, a displaced German, profoundly impacts the visionary dimension of her exile. The study uses a qualitative research method, specifically literary analysis within the framework of postcolonial and diaspora studies. The author depicts Arabs as humane, generous, peace-loving, and dignified people who suffer from political violence and displacement. They emphasize shared humanity, cultural richness, hospitality, and resilience, while challenging Western stereotypes that portray Arabs as violent or inferior. The study finishes with a compilation of topics that have affected Arab-Americans and shaped their cultural beliefs, including hybridity, multiculturalism, and identity deficiency. This research supports Arabic language learning by fostering cultural empathy and contextual understanding, enabling learners to engage with Arabic texts beyond stereotypes through authentic diasporic representations of Arab identity, values, and lived experience.